The crew - Copping, David1; Carroll, Matt; South Australian Film Corporation (North Ryde, NSW. : Australian Film Television & Radio School, 1981)
The film was made with the cooperation of the South Australian Film Corparation and the crew and cast of'Storm Bay'
The program illustrates the role of each film crew
Keywords: Film credits